ANALISIS FAKTOR PENENTU KEBERHASILAN PEMERINTAH DESA DALAM MENINGKATKAN EFEKTIVITAS PENGELOLAAN DANA DESA - Usman, U; Rahmawati, Fitri (Pusat Riset dan Publikasi, 2024)
This study aims to analyze the factors determining the government's success in increasing the effectiveness of village fund management, which is thought to consist of accountability, transparency and community participation. The type of this study was quantitative study with associative approach. The type of data used was quantitative obtained directly from primary sources using a questionnaire as a data collection instrument. The respondents for this study were the people of Baturotok Village, Batulanteh Sub-District, Sumbawa District, totaling 98 people. Data were analyzed using multiple linear regression analysis techniques, partial parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and coefficient of determination testing (). The result of this study showed that the accountability, transparency, and community participation had a a positive and significant effect on the effectiveness of village fund management, either partially or simultaneously. The ability of the accountability, transparency and community participation variables to effected the effectiveness of village fund management was 58.7% and is in the moderate category, while the remaining 41.3% was effected by other variables outside this research model, such as village apparatus competency, government internal control system, and accessibility of financial reports.